Epigenetic control of SPI1 gene by CTCF and ISWI ATPase SMARCA5 - Dluhosova, Martina; Curik, Nikola; Vargova, Jarmila; Jonasova, Anna; Zikmund, Tomas; Stopka, Tomas (PloS one, 2014)
CCCTC-binding factor (CTCF) can both activate as well as inhibit transcription by forming chromatin loops between regulatory regions and promoters. In this regard, Ctcf binding on non-methylated DNA and its interaction with the Cohesin complex results in differential regulation of the H19/Igf2 locus. Similarly, a role for CTCF has been established in normal hematopoietic development; however its involvement in leukemia remains elusive. Here, we show that Ctcf binds to the imprinting control region of H19/Igf2 in AML blasts. We also demonstrate that Smarca5, which also associates with the Cohesin complex, facilitates Ctcf binding to its target sites on DNA. Furthermore, Smarca5 supports Ctcf functionally and is needed for enhancer-blocking effect at ICR. We next asked whether CTCF and SMARCA5 control the expression of key hematopoiesis regulators. In normally differentiating myeloid cells both CTCF and SMARCA5 together with members of the Cohesin complex are recruited to the SPI1 gene, a key hematopoiesis regulator and leukemia suppressor. Due to DNA methylation, CTCF binding to the SPI1 gene is blocked in AML blasts. Upon AZA-mediated DNA demethylation of human AML blasts, CTCF and SMARCA5 are recruited to the -14.4 Enhancer of SPI1 gene and block its expression. Our data provide new insight into complex SPI1 gene regulation now involving additional key epigenetic factors, CTCF and SMARCA5 that control PU.1 expression at the -14.4 Enhancer.
Keywords: Leukemia, Myeloid; azacytidin; HeLa buňky; RNA interference; CCCTC-Binding Factor; regulace genové exprese u nádorů; konfokální mikroskopie; trans-aktivátory; metylace DNA; Chromosomal Proteins, Non-Histone; epigeneze genetická; Animals; Epigenesis, Genetic; insulinu podobný růstový faktor II; adenosintrifosfatasy; vazba proteinů; HeLa Cells; represorové proteiny; Humans; Microscopy, Confocal; akutní erytroblastická leukemie; imunoblotting; chromozomální proteiny, nehistonové; Immunoblotting; RNA Interference; RNA, Long Noncoding; CCCTC-vazebný faktor; Insulin-Like Growth Factor II; buňky K562; DNA Methylation; myeloidní leukemie; Cell Line, Tumor; K562 Cells; Genomic Imprinting; nádorové buněčné linie; zvířata; Trans-Activators; Gene Expression Regulation, Neoplastic; Azacitidine; akutní nemoc; Leukemia, Erythroblastic, Acute; Adenosine Triphosphatases; Repressor Proteins; polymerázová řetězová reakce s reverzní transkripcí; lidé; protoonkogenní proteiny; Acute Disease; genomový imprinting; RNA dlouhá nekódující; Proto-Oncogene Proteins; Reverse Transcriptase Polymerase Chain Reaction; Protein Binding